2001
DOI: 10.1007/s004640000336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased intraabdominal pressure on cardiac output and tissue blood flow assessed by color-labeled microspheres in the pig

Abstract: The level of IAP used in current practice (10-12 mmHg) appears to be safe with regard to hemodynamic variables and tissues blood flow; however, higher levels may induce a decrease in cardiac output and tissue blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
2
19
2
3
Order By: Relevance
“…Among such host factors, blood flow in the target tissue is an important determinant for the survival of tumor cells [4,5,10]. We have shown recently that pneumoperitoneum using CO 2 with intraabdominal pressure up to 15 mmHg has little influence on tissue blood flow in various intraabdominal organs [11]. However, preliminary data from this study suggested that the peritoneum responded differently to some extent.…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…Among such host factors, blood flow in the target tissue is an important determinant for the survival of tumor cells [4,5,10]. We have shown recently that pneumoperitoneum using CO 2 with intraabdominal pressure up to 15 mmHg has little influence on tissue blood flow in various intraabdominal organs [11]. However, preliminary data from this study suggested that the peritoneum responded differently to some extent.…”
contrasting
confidence: 45%
“…The absorbency was determined as a specific absorbance for each color. The tissue blood flow rate and cardiac output were calculated as previously described [11].…”
Section: Blood Flowmentioning
confidence: 99%
“…Low insufflations pressure in group A might attributed to the unaltered plasma sodium, potassium and chloride as reported by Yavuz et al 22 Furthermore, CP maintained for only 30 minutes in animals of the present study might be insufficient to inflict any changes. 23 Two cytosolic enzymes ALT and AST are mostly used to evaluate hepatic function.…”
Section: Effect Of Different Carbon Dioxide Pressure Gradients In Capsupporting
confidence: 53%
“…Two experimental studies by Rosenthal et al 9 and Ben-Haim et al showed the increase in IAP to be followed by an increase in systolic, diastolic and mean arterial pressure, as well as in CVP. Th e study conducted by Yavuz et al 11 , inducing IAH in experimental conditions of pneumoperitoneum, showed that an increase in IAP caused an increase in arterial blood pressure, PaCO 2 and PaO 2 , whereas SpO 2 remained unchanged. Also, in the study by Barnes et al 12 it was demonstrated that at very high levels of IAP there was an increase in blood pressure, whereas heart rate did not change, PaO 2 decreased and PaCO 2 increased.…”
Section: Discussionmentioning
confidence: 98%